Pulping Qualities of Eucalyptus ’Hybrid’ Grown in U.P - Guha, S. R. D.; Sharma, Y. K.; Pant, Rajesh S. P.; Jain, D. K.; Karira, B. G. (Indian Forester, 1973)
Results of pulping qualities or Eucalyptus ’hybrid’ (Mysore Gum. mostly E. tereticornis) grown in various localities or Uttar Pradesh are recorded. Attempts have also been made to study the effect of age, rate or growth and top, middle and bottom portion of the main bole on pulping qualities. The results indicate that Eucalyptus ’hybrid’ grown in Taral and Bhabar Division, Barkot Range, Lachhlwala Range, Bijnor Plantation Division or in Shivalik Range is equally suitable ror pulp and papermaking. There is an indication that up to 9 years of age the strength properties of pulp improves. No significant difference was round in pulp quality when sample for different rate of growth and top, middle and bottom portion were pulped using same pulping conditions.